The role of vitamin D receptor gene polymorphisms in Turkish infants with urolithiasis. (20th April 2016) - Goknar, Nilufer; Öktem, Faruk; Torun, Emel; Gok, Ozlem; Demir, Aysegul Dogan; Kucukkoc, Mehmet; Kilic, Ulkan
Abstract: Polymorphisms in the vitamin D receptor (VDR) gene have recently been reported to be associated with urinary calculi in pediatric and adult cases, but no studies have looked at the youngest period of life. The purpose of this study was to investigate the role of VDR gene polymorphisms in infantile urolithiasis in a Turkish population. We compared a study group of 104 infants (55 girls and 49 boys, mean age 6.94 ± 3.81 months) with a control group of 96 infants (51 girls and 45 boys, mean age 7.51 ± 3.23) to evaluate their demographics and metabolic risk factors. PCR-based restriction analysis of the polymorphisms on the VDR gene (BsmI and TaqI) showed statistically significant differences between study and control groups ( p  = 0.001 and 0.043, respectively). In addition, the prevalence of the BsmI genotype was significantly different between the hypercalciuric and normocalciuric stone formers ( p  = 0.007). Allelic frequencies were similar between the urolithiasis and control groups ( p  > 0.05). The B allele of BsmI and the A allele of ApaI were more prevalent in the hypercalciuric stone formers than in the normocalciuric stone formers ( p  = 0.018 vs.0.036, respectively). These results suggest that the BsmI and TaqI VDR genotypes could be candidate genes leading to infantile urolithiasis.